Analysis of chronic disease comorbidity patterns in middle-aged and elderly smokers in China: The China Health and Retirement Longitudinal Study - Shanwen Sun; Yali Wang; Hailong Hou; Linlin Chen; Yuqi Niu; Yefan Shao; Xiaochun Zhang (PLoS ONE, 2025)
Background China has the largest tobacco consumer population in the world, and with the increasing severity of aging, the health issues caused by smoking continue to draw attention. This study aims to explore the current state of chronic disease comorbidity under different smoking patterns, providing a foundation for the formulation of public health policies. Methods A total of 10771 participants older than 45 were included from CHARLS collected in 2020 after screening. The research variables were extracted and processed using Stata 18.0 software, followed by data filtering and organization in Excel. Through chi-square tests and multinomial logistic regression analysis, the study explored the influencing factors of comorbidity patterns under different smoking statuses. Results The results indicate that within the framework of multiple chronic conditions, 2,254 individuals (20.9%) were relatively healthy, while 79.1% had one or more chronic conditions: 3,656 in the simple chronic disease group (33.9%), 3,998 in the minor complex chronic disease group (37.1%), and 863 in the major complex chronic disease group (8.0%). The severity of comorbidity patterns was significantly associated with age, alcohol consumption, hospitalization in the past year, outpatient visits in the past month, insufficient sleep, and poor cognitive function across different smoking statuses. Additionally, living in urban areas and having depression were linked to higher comorbidity severity among non-smokers. Among smokers, being female and having low life satisfaction were independent risk factors for comorbidity patterns. In the group of former smokers, intense physical activity was associated with an increased risk of severe comorbidity patterns. Conclusion In response, it is recommended to strengthen public health strategies and interventions related to chronic disease comorbidity among smokers.